INDICATORS CELL CYCLE AND DNA FRAGMENTATION IN CELLS OF SMALL INTESTINE MUCOSA 14, 21 AND 30 DAYS AFTER SKIN BURNS ON THE BACKGROUND OF PRE-LIMINARY INFUSION OF SOLUTION LACTOPROTEIN WITH SORBITOL OR HAES-LX 5% - Gavryluk, A.O.; Galunko, G.M.; Chereshniuk, I.L.; Tikholaz, V.O.; Cherkasov, E.V.; Dzevulska, І.V.; Kovalchuk, О.І. (World of Medicine and Biology, 2018)
In analyzing the data of cell cycle and DNA fragmentation of the cells of the mucous membranes of the small intestine of rats in the late stages after the thermal burn of skin 2-3 degrees, in the area of 21-23% of the body surface, on the background of the previous use of infusion solutions, it was found that "lactoprotein with sorbitol" or HAES-LX-5% have a positive effect on cell cycle performance: after 14 days, the S-phase data and the index of proliferation were increased compared with those in the burn group + 0.9% NaCl solution in the same period; after 21 days, the S-phase data and the index of proliferation of these two groups were significantly higher than those in the burns + 0.9% NaCl solution, and at the same time, the values of the SUB-G0G1 interval in both groups were lower than those in the group where was used 0,9% NaCl solution on the background of burn. After 30 days in the burn + HAES-LX-5% group, all cell cycle indices have no significant or trend-specific differences compared to those in the non-burning group, and with "lactoprotein with sorbitol", the G0G1 and the proliferation phases have been significantly lower than indicators in a group without skin burns.
Keywords: cell cycle; DNA cytometry; small intestine; rats; thermal burn skin; "lactoprotein with sorbitol"; HAES-LX 5%